Metabolic conditioning among soccer players - Rhea, M. R.; Lavinge, D. M.; Robbins, P.; Esteve-Lanao, J.; Hultgran, T. L. (The Journal of Strength and Conditioning Research, 2009)
To reduce the risk of overuse injuries, yet obtain optimal fitness development among soccer players, research comparing different training strategies is required. This study compared conventional group conditioning (GRP) to individualized training (IT) during the preseason among female college soccer players. Both groups participated in soccer practices; however, players were randomly assigned to supplemental conditioning differentiated by the use of player-specific heart rate training in the IT group. Changes in maximal oxygen consumption, anaerobic threshold, and rate of recovery were analyzed before and after 12 weeks of conditioning. Data analysis identified significantly (p < 0.05) greater improvements in the IT group in all 3 variables, despite considerably less training volume. Based on these data, it is apparent that catering training to the fitness level of each individual player can have a positive impact on training adaptations.